The Wind Velocities Driven by Alfven Waves in 31 CYG - Kyung-Mee Kim; Kyu-Hong Choi (Journal of Astronomy and Space Sciences, 1991)
31 Cyg is a ζ Aur-type eclipsing long-period binary composed a K supergiant and a hot main sequence star. Superginats have massive cool winds with low terminal velocities, and it is generally believed that supergiant's winds are driven by Alfven waves. We have calculated the wind velocities for 31 Cyg by integrating of equation of motion due to Alfven waves and the results are agreed with observational terminal velocities. And our results are compared to Kuin and Ahmad's semiempirical wind model (1989).